Concretização de um consumo sustentável a partir da democratização das economias circular e verde - Ritter, Lídia de Paola (2020)
This work seeks to analyze the way in which the phenomenon of globalization influences exacerbated consumption and the impacts that such practices cause to the environment in today's society. It is observed that everything revolves around hyperconsumption, and society in general only feels satisfied and happy if they buy/acquire what advertising, through the phenomenon of globalization, makes reach the future consumer instantly as news. The objective of this dissertation is to investigate ways of democratizing Circular and Green Economy Theories, so that sustainable consumption and environmental protection can be achieved. To this end, the first chapter addresses the phenomenon of globalization, economic growth and decline. The second chapter explains the paradigms of sustainable development based on UN guidelines, as well as the pillars of sustainability for the correct application of circular and green economies. The third and final chapter addresses Circular and Green Economies as ways to democratize sustainable consumption in a globalized world. Furthermore, it deals with the application of theories as ways to democratize sustainable consumption in a globalized world. As for the methodology, the research is conducted using the hypothetical-deductive scientific method through a qualitative investigation. The procedural criterion used is monographic. As an instrument for carrying out the investigative process, documentary and bibliographic techniques are used, supported by normative instruments and international and national legislation.